THE SIGNIFICANCE OF UNIFORMITY IN KATHAK NRITTA HASTA - Vats, Parul Purohit (ShodhKosh: Journal of Visual and Performing Arts, 2023)
This paper talks about the significance of uniformity in the Nritta Hastas of Kathak dance across gharanas and eras. Kathak, an Indian classical dance form, hails from North India. Nritta Hastas refer to hand gestures or movements used in Indian classical dance. Often interchanged with” “hasta mudra”, “Nritta Hastas” encompass all hand movements and gestures, whereas “mudras” are more indicative of emotions and literal depictions of objects present in our environment. Kathak has evolved to appeal and cater to the spectators of today’s times - with lightning fast spins and hand movements along with intricate footwork. However, this has caused unfavorable negotiations with the original technique and overall uniformity of Nritta Hastas, thus resulting in the deterioration of quality in dance performances. For example, prioritizing the ability to execute multiple spins in quick succession, aiming to impress the audience with their speed and agility, leads to neglecting the intricate hand movements and mudras, which are essential for conveying the nuanced emotions and storytelling aspects of the dance. The purpose of this research paper is to shed light on the importance of maintaining uniformity by adhering to techniques, methods and pedagogies mentioned in ancient scriptures pertinent to Indian classical dance.